Determination of Extended-Spectrum β-Lactamases and AmpC Production in Uropathogenic Isolates of Escherichia coli and Susceptibility to Fosfomycin - Gupta, Varsha; Rani, Hena; Singla, Nidhi; Kaistha, Neelam; Chander, Jagdish (Journal of Laboratory Physicians, 2013)
Background: Urinary tract infection due to Escherichia coli is one of the common problem in clinical practice. Various drug resistance mechanisms are making the bacteria resistant to higher group of drugs making the treatment options very limited. This study was undertaken to detect ESBLs and AmpC production in uropathogenic Escherichia coli isolates and to determine their antimicrobial susceptibility pattern with special reference to fosfomycin.Materials and Methods: A total number of 150 E. coli isolates were studied. ESBL detection was done by double disc synergy and CLSI method. AmpC screening was done using cefoxitin disc and confirmation was done using cefoxitin/cefoxitin-boronic acid discs. In AmpC positive isolates, ESBLs was detected by modifying CLSI method using boronic acid. Antimicrobial susceptibility pattern was determined following CLSI guidelines. Fosfomycin susceptibility was determined by disc diffusion and E-test methods.Results: ESBLs production was seen in 52.6% of isolates and AmpC production was seen in 8% of isolates. All AmpC producers were also found to be ESBLs positive. ESBLs positive isolates were found to be more drug resistant than ESBLs negative isolates. All the strains were found to be fosfomycin sensitive.Conclusions: ESBLs and AmpC producing isolates are becoming prevalent in E. coli isolates from community setting also. Amongst the oral drugs, no in-vitro resistance has been seen for fosfomycin making it a newer choice of drug (although not new) in future. An integrated approach to contain antimicrobial resistance should be actually the goal of present times.
Keywords: AmpC; E. coli; extended-spectrum β-lactamases; fosfomycin; urinary tract infection